Button pusher - Page, Tyler, 1976- (First Second, 2022)
A graphic novel dramatizing the author's experiences as a preteen with ADHD, a time when he had great difficulty paying attention in class and seemed unable to control how he acted, often being goofy and immature, and sometimes dangerous. Explores how Tyler was diagnosed with ADHD and how after that he slowly learned to manage his medications and deal with his symptoms, not to mention his social problems, like his parents' fighting.